Tanggung Jawab Sosial dan Rasio Keuangan terhadap Tax Avoidance - Jemima Octaviani; Yulius Kurnia Susanto; Iman Akhadi (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to provide empirical evidence about the factors that affect tax avoidance. These factors are: corporate social responsibility, leverage, independent commissioners, audit quality, profitability, and sales growth on tax avoidance. The population in this research is manufacturing companies that listed in Indonesia Stock Exchange from 2018-2020. The sample used for this research consist of 73 listed manufacturing companies. This study uses purposive sampling method and the data obtained from these samples were analyzed using multiple regression analysis. The results of this research show that profitability have effect ontax avoidance. However, corporate social responsibility, leverage, independent commissioners, audit quality, and sales growth have no effect on tax avoidance.